Model Pembelajaran Kooperatif Tipe Student Team Achievement Divisions (STAD) terhadap Kemampuan Representasi Matematis Siswa Kelas VIII SMPN 2 Tambusai Utara - Arcat; Amri Subchan (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2019)
This study aims to look at the effect of the STAD type cooperative learning model on the mathematical representation ability of class VIII students of SMPN 2 Tambusai Utara. The research method used is quasi-experiment involving two classes, namely as a control class and an experimental class. The research was conducted at SMP Negeri 2 Tambusai Utara Academic Year 2018/2019 which involved classes VIII a and VIII b. The students' mathematical representation ability test instrument used 3 questions in the form of descriptions. Data analysis was performed using SPSS with Liliefors Test as data normality test, Fisher Test as Homogeneity test data and t-test for average similarity test. The results of the study revealed that there was an influence of the STAD type cooperative learning model on the mathematical representation ability of students, meaning that the value of the representation of the experimental class students was better than the value of the control class. The average obtained by the experimental class was 77.27, while for the average value of the control class was 67.74.